"Base, but Nevertheless Holy": Lessons in Liminality from Symeon the Holy Fool. (December 2014) - Johnson, Christopher DL
Victor Turner briefly mentions the liminality of "holy beggars" and "simpletons" (1969: 110) but this point has received little attention in existing literature on either liminality or holy fools. The seventh-century saint's life The Life of Symeon the Fool is often described as presenting Symeon as someone who challenges and inverts norms while ultimately remaining a "loyal, albeit restless, member" of Emesa's Christian community (Saward, 2000: 28). This paper will argue that Symeon's prolonged liminality in the narrative allows him to play both of these roles by blurring the lines between desert and city, compassion and aggression, and critic and caretaker.